Revisiting PQ4R and CSR for Teaching Reading Skills for Adolescents - Ryan Oktarini; Sugirin Sugirin (Journal of English Language Teaching and Linguistics, 2019)
The developing technonolgy brings the teenagers to the world interaction without boundary. Teenagers, or adolescents, are demanded to be able to master English. Thus, teaching and learning reading skills has become one essential factor to help them to master English. The aims of this research are to find out the effectiveness of PQ4R and Collaborative Strategic Reading on students’ reading skill development for adolescents; (2) to find out the most effective technique for teaching reading skill for adolescents. This study was a quasi-experimental research with two experimental groups and one control group. The three variables used were PQ4R, Collaborative Strategic Reading (CSR), and Conventional techniques. The sample of this study were grade X Science 1, X Social 1 and X Social 2 who had homogenous reading level who were selected by using Cluster Random Sampling. The quantitative data were collected by using pretest and posttest to assess the reading comprehension. The result indicated that there was a difference in the students’ reading achievement given different treatment. Students taught using PQ4R had an improvement from 61.75 to 71.63 while students taught using CSR had improvement from 63.32 to 75.50. Students taught using conventional technique also indicated improvement from 62.5 to 68.38. The most effective technique was CSR compared to PQ4R and Conventional techniques. The improvement of students’ reading skill development reach 15.9% while the improvement using PQ4R was 19.25% 9 and using conventional technique was 9.28%. Therefore, it can be concluded that CSR was the most effective technique for teaching reading skills for adolescents compared to PQ4R and conventional techniques